Studi Komparatif Model-Model Integrasi Pembelajaran Berdiferensiasi dan Deep Learning untuk Mendukung Competency Based Learning - Intan Nurjannah; Shalihatul Kamala; Agung Setyawan (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to analyze the comparison of various integration models between differentiated learning and deep learning approaches to support the implementation of competency based learning (CBL). The study focused on the effectiveness of the combination of the two approaches in increasing the meaning of the learning process and the achievement of students' competencies. The research method used is in the form of qualitative methods or literature studies by reviewing various literature related to the concept of differentiated learning, deep learning, differentiated learning integration models and deep learning to support competency based learning. The results of the study found several integration models such as the adaptive instructional model based on DI+diagnostic technology and project-based deep differentiation, a  combination of differentiated learning, which is oriented to the individual learning needs of students, and deep learning, which emphasizes the deepening of concepts, creating complementary relationships. These two approaches have been shown to be more effective in increasing students' active involvement, developing critical thinking skills, and strengthening competency achievement than applying one approach separately. The conclusion  of this study confirms that the application of an integrative model developed through a literature review shows that differentiated learning and deep learning can play a role as an effective strategy to optimize the implementation of competency based learning.